In-orbit aerodynamic coefficient measurements using SOAR (Satellite for Orbital Aerodynamics Research). (March 2021) - Crisp, N.H.; Roberts, P.C.E.; Livadiotti, S.; Macario Rojas, A.; Oiko, V.T.A.; Edmondson, S.; Haigh, S.J.; Holmes, B.E.A.; Sinpetru, L.A.; Smith, K.L.; Becedas, J.; Domínguez, R.M.; et al.
Abstract: The Satellite for Orbital Aerodynamics Research (SOAR) is a CubeSat mission, due to be launched in 2021, to investigate the interaction between different materials and the atmospheric flow regime in very low Earth orbits (VLEO). Improving knowledge of the gas–surface interactions at these altitudes and identification of novel materials that can minimise drag or improve aerodynamic control are important for the design of future spacecraft that can operate in lower altitude orbits. Such satellites may be smaller and cheaper to develop or can provide improved Earth observation data or communications link-budgets and latency. In order to achieve these objectives, SOAR features two payloads: (i) a set of steerable fins which provide the ability to expose different materials or surface finishes to the oncoming flow with varying angle of incidence whilst also providing variable geometry to investigate aerostability and aerodynamic control; and (ii) an ion and neutral mass spectrometer with time-of-flight capability which enables accurate measurement of the in-situ flow composition, density, velocity. Using precise orbit and attitude determination information and the measured atmospheric flow characteristics the forces and torques experienced by the satellite in orbit can be studied and estimates of the aerodynamic coefficients calculated. This paper presents the scientific concept and design of the SOAR mission. The methodology for recovery of the aerodynamic coefficients from the measured orbit, attitude, and in-situ atmospheric data using a least-squares orbit determination and free-parameter fitting process is described and the experimental uncertainty of the resolved aerodynamic coefficients is estimated. The presented results indicate that the combination of the satellite design and experimental methodology are capable of clearly illustrating the variation of drag and lift coefficient for differing surface incidence angle. The lowest uncertainties for the drag coefficient measurement are found at approximately 300 km, whilst the measurement of lift coefficient improves for reducing orbital altitude to 200 km. Highlights: The design of the experimental CubeSat SOAR (Satellite for Orbital Aerodynamics) is presented. SOAR is due to be launched in early 2021 to the ISS and subsequently deployed into orbit. The mission will perform the aerodynamic characterisation of materials in very low Earth orbit (VLEO). The aim is to improve understanding of the fundamental gas–surface interactions in the VLEO environment. Materials able to reduce aerodynamic drag and improve aerodynamics-based control will be tested.